2022
DOI: 10.2147/opth.s385806
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Diabetic Retinopathy among Adult Diabetes Patients in Southeast Ethiopia: A Hospital-Based Cross-Sectional Study

Abstract: Background Diabetic retinopathy (DR) is the most prevalent microvascular consequence of diabetes mellitus, and it can result in blindness that is irreversible. Due to delayed diagnosis and limited access to diabetic care, the situation is even worse in developing countries. Scientific evidence on the prevalence of DR and its associated factors among diabetes patients in low-income countries, such as Ethiopia, is limited. This study aimed to determine the prevalence of DR and associated factors amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, Sasso et al have reported that higher HDL‐C could be a risk factor for DR 39 . Other studies have suggested that a higher HDL‐C level was associated with a reduced prevalence of DR 40,41 . The disparity of these findings suggests that the relationship between HDL‐C and DR may be complicated and is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Sasso et al have reported that higher HDL‐C could be a risk factor for DR 39 . Other studies have suggested that a higher HDL‐C level was associated with a reduced prevalence of DR 40,41 . The disparity of these findings suggests that the relationship between HDL‐C and DR may be complicated and is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with a previous prospective study that indicated a connection between HDL-C and renal events, but not between HDL-C and retinal events in patients with T2D. However, Sasso et al have reported that higher HDL-C could be a risk factor for DR. 39 Other studies have suggested that a higher HDL-C level was associated with a reduced prevalence of DR. 40,41 The disparity of these findings suggests that the relationship between HDL-C and DR may be complicated and is still unclear. Interestingly, an obvious interaction between sarcosine and HDL-C on DR was observed in our study.…”
Section: Biological Rationalitymentioning
confidence: 99%
“…The twenty-six studies [20,25,26,, six studies [57][58][59][60][61][62] and two studies [63,64] were conducted using cross-sectional, retrospective cohort and case-control study designs respectively. Regarding geographical region, seventeen studies [20, 25, 26, 35, 36, 38, 40, 43, 45, 49-51, 55, 56, 60-62] were conducted in Amhara, eight studies [39,41,44,48,52,58,59,63] were conducted in Oromia, five studies [42,46,53,57,64] were conducted in Addis Ababa, three studies [37,47,54] were conducted in Southern nations, nationalities and peoples, and one study [34] was conducted in Sidama region.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Five studies [35,38,44,49,56] showed that obesity was significantly associated with visual impairment. The pooled AOR of visual impairment for diabetes patients having obesity was 4.77 (95% CI: 3.00, 7.59; I 2 = 0%; P<0.93).…”
Section: Factors Associated With Visual Impairmentmentioning
confidence: 99%
“…Longterm diabetes management is important in delaying the progression of eye complications. Improved lipid profile and hypertension control can also slow the progression of retinopathy, especially when initiated soon after the diagnosis of diabetes [13].…”
Section: Thementioning
confidence: 99%